John Galt and the Horizons of the Firth of Clyde - McKeever, Gerard (Romanticism on the Net)

(untitled) (Université de Montréal, 2022)
This article discusses the cultural geography developed by John Galt across several decades in his writing, from his travel writing in the early 1810s, through his 1820s fiction, to his autobiographies and North American novels in the 1830s. At the centre of this are Galt’s influential accounts of the southern side of the Firth of Clyde in the 1820s, described here in terms of a dialectical regionalism that is rarefied under the pressure of migration and mobility. Place, in this context, is a social text brought into being by the negotiation of its horizons. The article situates Galt’s attention to this coastal region of Scotland—in and beyond his “Tales of the West”—within British imperial, European, and transatlantic contexts, while examining the early nineteenth century’s culture of literary home-longing. Despite continuities with his earlier writing, Galt’s best-known work reflects a distinctively 1820s cultural watershed, suffused as it is by ethnographic and autoethnographic versions of regional difference. In fact, Galt’s system of local-global attachment potentially relegates the nation to subordinate status, so that “Scotland” where it appears presents a synecdoche for a portion of the western seaboard, rather than the other way around. As it progresses, the article brings Galt’s development of home-longing into dialogue with his active colonialism, concluding that this marks the sharp horizons of sympathy, and the unequal power relations, in this version of literary belonging.